Comparative Perspective on Customs Offences: Romania and the Republic of Moldova in the Legal and Customs context - Mercus, Radu (Acta Universitatis Danubius. Juridica, 2024)
This study comparatively analyzes the contraventions and customs offenses in Romania and the Republic of Moldova, in the legal and customs context specific to each country. In this sense, both the legislative differences and the similarities between the two states are highlighted. The research explores the historical developments of customs regulations, the constituent elements of customs contraventions and offences, and applicable sanctions. Finally, the paper aims to contribute to a deeper understanding of the customs criminal phenomenon and to provide a basis for reflection for improving legislation in the field.